Emotional dependence as a predictor of dating violence in peruvian university men - Perez Dominguez, Geison (2022)
Objective: The objective of this study was to evaluate whether emotional dependency significantlypredicts dating violence in Peruvian male university students. Methodology: A cross-sectionalpredictive design was used for the study. The sample consisted of 314 male students from theUniversidad Peruana Unión, whose ages ranged from 18 to 30 years (M=23.11, SD=3.253). Results:The results showed that 48.4% of the population presented emotional dependence and 49.7% reportedhaving been victims of violence, the most prevalent being verbal violence (44.6%) and prohibition(43.6%). When establishing the correlation between emotional dependence and violence, a direct andstatistically significant relationship was found (p <.05). Conclusion: Emotional dependence (p < .05)is a variable that significantly predicted violence (R=.250). It is concluded that presenting emotionaldependence predicts the appearance of violent behaviors in the dating relationship in university males.